Pengaruh Konsentrasi Daging Buah Gandaria Terhadap Permen Jelly Rumput Laut (Eucheuma cottonii) - Notanubun, Talia H; Tuhumury, Helen C D; Nendissa, S J (Universitas Pattimura, 2023)
The purpose of the research was to determine the chemical, physical and organoleptic characteristics of jelly candy with the addition of gandaria flesh. This study used a single randomized complete design with 5 treatment level and 2 replications. The treatment levels in this study were: P1 (Meat Gandaria), P2 (25% Meat Gandaria), P3 (50% Meat Gandaria), P4 (75% Meat Gandaria), P5 (100% Meat Gandaria). The results showed that the treatment using doubles flesh was better than the others because it had a water content (16,70%), ash content (0,92%), total sugar (23,71%), pH (5,25%), total acid (8,05%). The seaweed jelly candy turned out to be preferred by panelists in all categories of hedonic of taste (2,65%), aroma (2,35%), color (2,65%), texture (2,7%), general acceptance (2,9%), level of acidity (2,35%).